PERBANDINGAN WAKTU MOBILISASI PASCA ANESTESI SPINAL PADA PASIEN SECTIO CAESAREA DENGAN METODE ERACS DAN NON ERACS DI RSU HERMINA PADANG - Anita Darmayanti; Mashdarul Ma’arif; Nadya Nabila Vedrin (Yayasan Nusantara Hasana Berdikari, 2026)
Cesarean section is a surgical procedure to deliver a fetus through an incision in the abdominal wall and uterus, which generally uses spinal anesthesia. One innovation to accelerate postoperative recovery is the Enhanced Recovery After Cesarean Surgery (ERACS) method, which integrates pre-, intra-, and postoperative management to accelerate patient mobilization. Assessment of motor recovery after spinal anesthesia can be measured using the Bromage Score. This study aimed to compare the time to achieve the Bromage Score as an indicator of patient mobilization after spinal anesthesia in cesarean section surgery with the ERACS method and non-ERACS at Hermina Padang General Hospital. This study used a comparative analytical design with a cross-sectional approach. The sample consisted of 36 patients who underwent cesarean section surgery with spinal anesthesia at Hermina Padang General Hospital, which were divided into two groups: 18 patients with the ERACS method and 18 patients with the non-ERACS method. Data were analyzed univariately and bivariately using the independent t-test if the data were normally distributed and the Mann-Whitney test if the data were not normally distributed. Most patients were aged 26–35 years (80.6%), with the majority being nulliparous and primiparous (38.9%), and the majority having never undergone a cesarean section (55.6%). The mean time to achieve the Bromage Score showed that the ERACS group recovered faster than the non-ERACS group. The test results showed no significant difference in Bromage Score 3 (p = 0.825), but significant differences in Bromage Score 2 (p = 0.039), Bromage Score 1 (p = 0.000), and Bromage Score 0 (p = 0.046). The ERACS method has been shown to accelerate lower extremity motor recovery after spinal anesthesia compared to the non-ERACS method in cesarean section patients at Hermina Padang Hospital.